Stabilization of aluminum doped zinc oxide nanoparticle suspensions and their application in organic solar cells - Wolf, N.; Stubhan, Tobias; Manara, J.; Dyakonov, Vladimir; Brabec, Christoph (Thin Solid Films, 2014)
Aluminum doped zinc oxide (AZO) nanoparticles were redispersed in isopropyl alcohol and stabilized with different stabilizers and mixtures of stabilizers that allow for electronically functional particles. The size of the redispersed nanoparticles was small enough to use these suspensions to build interfacial layers in inverted polymer-fullerene solar cells. The performance of these devices was found to depend on the stabilizer used in the nanoparticle suspension. The best performance was obtained with an AZO interfacial layer built with a 3,6,9-trioxadecanoic acid and polyvinylpyrrolidone stabilized nanoparticle suspension. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aluminum doped zinc oxide; Nanoparticle suspensions; Interfacial layers; Inverted polymer-fullerene solar cells